Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0254451
|View full text |Cite
|
Sign up to set email alerts
|

Association between type 2 diabetes and osteoporosis risk: A representative cohort study in Taiwan

Abstract: Although previous studies have investigated the relationship between fracture risk and type 2 diabetes (T2D), cohort studies that estimate composite osteoporosis risk are lacking. This retrospective cohort study sought to determine the risk of osteoporosis in Taiwanese patients with T2D. Patients diagnosed with T2D between 2002 and 2015 identified through the 2002 Taiwan Survey of Hypertension, Hyperglycemia, and Hyperlipidemia were included. A total of 1690 men and 1641 women aged ≥40 years linked to the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
2
18
0
1
Order By: Relevance
“…Type 2 diabetes mellitus is significantly associated with osteoporosis risk. A study by Lin et al from Taiwan concluded a positive association between the presence of type 2 DM and the incidence of osteoporosis [ 52 ]. Another small sample, cross-sectional study revealed no significant difference in bone density between diabetic and nondiabetic subjects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus is significantly associated with osteoporosis risk. A study by Lin et al from Taiwan concluded a positive association between the presence of type 2 DM and the incidence of osteoporosis [ 52 ]. Another small sample, cross-sectional study revealed no significant difference in bone density between diabetic and nondiabetic subjects [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that ectopic fat deposition may be the reason for insulin resistance. Owing to some mechanisms, like the changes of bone microstructures by hyperglycemia, chronic inflammation and accumulation of advanced glycation end products, the osteoblast metabolism and maturation can be harmed ( 15 ), resulting in lower muscle mass, strength and bone mineral density in these patients. Other studies have shown that osteoporosis and paraspinal muscle degeneration may interact and coexist in patients with degenerative lumbar disorders ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…T2DM was connected favorably with osteoporosis occurrences in a Taiwanese population, with the association being stronger among the elderly, and T2D was strongly linked to the risk of osteoporosis., regardless of gender nonelderly participants, in particular [19]. Osteoporosis can affect men and women, especially those who are older.…”
Section: Discussionmentioning
confidence: 99%